Efficient home energy management based on the Colombian Law 1715/2014 - Vega Escobar, Adriana Marcela (2016)
This paper proposes a home energy management model called GEDE, outlined in the Colombian Law 1715/2014 [1], taking into account the considerations proposed in chapters II and III related to electricity production with non-conventional energy sources, efficient energy management as well as incentives to invest in this kind of projects. Different operation ways that can be applied in the proposed residential energy system are presented. The system has a variable topology, so this is feed by distributed generation sources or by the interconnected system and they are related to a control system that allows the incorporation of bi-directional metering to establish the electric flow as well as its protections. Three scenarios were analyzed; the first one corresponds to work with distributed generation during peak hours and the user manually activates the system; the second one consists in selecting the critical loads, which keep connected to the distribution system while the use of the other loads is postponed until next hour, thus this scenario is semiautomatic. In the third scenario the system saves energy in an autonomous way through intelligent infrastructure controlling the appliances and lighting utilization. This proposal allows providing new energy consumption patterns through mechanisms that make a significant contribution to the efficient energy by utilizing monitoring, control and supervision techniques together with distributed generation.